Business process maturity assessment in micro, small, and medium-sized enterprises - Badriyah, Nurul; Tajudeen, Farzana Parveen; Muhtarom, Abid; Ika, Siti Rochmah; Rahmawati, Rahmawati (International Journal of Innovative Research and Scientific Studies, 2025)
This research looks at how developed the business processes are in micro, small, and medium enterprises (MSMEs) in Indonesia, focusing on how leadership commitment, process documentation, employee skills, and performance measurement affect organizational agility as a moderating factor. The study employed quantitative research methods, collecting data from a total of 235 respondents representing MSMEs in Indonesia. The results were obtained using multiple linear regression analysis, which examined how the independent variables are directly connected to the dependent variable of business process maturity, while the influence of organizational agility was assessed through interaction terms. Our findings reveal that leadership commitment, process documentation, employee competence, and performance measurement had positive and significant impacts on business process maturity among MSMEs. Likewise, the analysis reveals that organizational agility positively moderates the relationship between internal antecedents and structured as well as mature business processes, which shows that MSMEs' agility enhances their inclination to convert internal abilities to processed business activities. This paper is the first to look at how organizational agility affects the link between the business process maturity of MSMEs and their performance, a topic that hasn't been widely studied, especially in emerging economies. It is a holistic model that recognizes the importance of visionary capabilities in relation to running highly efficient processes. The results indicate that enhancing both leadership and operational capabilities would be a priority area for business process maturity among MSMEs. This knowledge must help MSMEs become more resilient and competitive, contributing to the economy and being sustainable.